The study of media acceptance and spotify services between Malaysia and United States of America (U.S.A) scales / Edriz Imran Ramli - Ramli, Edriz Imran (2022)
Spotify transformed music listening forever when it launched in 2008. Anyone can have the access to listen to free music. As of July 2020, Spotify has around 300 million monthly active users, including 138 million paying subscribers. In year 2021, Spotify subscribers climbed to 165 million subs, and 81 million of them are in the U.S. A, which are North America and Latin America. With millions of users for Spotify, there will be either positive or negative reviews. This study focuses on the media acceptance and Spotify services between Malaysia and united states of America (U.S. A). The objective of this study is to study the company's business conduct between Malaysia and U.S.A, and to analyse the level of media acceptance among Malaysia vs U.S.A. The methodology of this research is will be conducted qualitatively in order to generalise the result by using thematic analysis. Since this study does not conduct physical and virtual interviews, a qualitative method through descriptive ethnographic research and content analysis is used. Music became an important factor and source of filling people's empty emotion. Instead of measuring the satisfactory of music types and genres, this study focus on measure a specific aspect of the Spotify application that provides music for people. Other streaming platform are not included in this research, as it has to be about Spotify app only. The study was well-conducted, and the information obtained differs in percentage terms between international and local data, despite the fact that the total amount for both international and local data is the same, which is 50 each.